Development of aluminum alloy/galvanized steel joining method using refill friction stir spot welding. (3rd June 2022) - Takeoka, Naoki; Miyama, Takuma; Matsuda, Tomoki; Ogura, Tomo; Ohashi, Ryoji; Hirose, Akio
Abstract: Friction stir spot welding (FSSW) is one of the solid-state welding method and dissimilar material joining by FSSW has been investigated. However, a removable coating is required to form a clean surface on the lower plate in conventional FSSW method. Therefore, we have developed a new dissimilar material joining method – scrubbing refill FSSW (Sc-RFSSW) – and Sc-RFSSW provides higher joint strength than conventional FSSW methods in joining the aluminum alloy and non–coated mild steel. In this study, the mechanical properties and metallurgical joining interface of an aluminum alloy and a hot-dip galvanized (GI) coated steel joint by Sc-RFSSW were investigated. In addition, a new tool tip shape was examined to improve the interfacial cleaning effect.